Computation of current-resistance photovoltaic model using reverse triangular number for photovoltaic emulator application - Razman Ayop; Chee Wei Tan; Kwan Yiew Lau (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
PV emulator (PVE) is a power supply that produces similar current‑voltage (I‑V) characteristic as the PV module. It simplifies the testing of the PV system during the development phase. Since the output voltage and current of the PVE change based on various factors (load, irradiance and temperature), the computation of the operating point for the PVE is crucial. The resistance feedback control strategy is a robust and fast approach to find the operating point for the PVE. Nonetheless, it uses an uncommon current‑resistance PV model, which cannot be computed using the conventional approach. This work introduces the reverse triangular number to compute the PV model and obtained the operating point of the PVE. The reverse triangular number is based on the variable step sizes that allow fast computation of the PV model. The operating point is then used by the PI controller and the buck converter to produce the output voltage and current similar to the PV module. The results show that the reverse triangular number is able to compute the PV model accurately. In addition, the proposed PVE not only works well with resistive load but adapts accurately under the integration with maximum power point tracking converter.